2011
DOI: 10.3892/mmr.2011.535
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide inhibits gastric cancer cell growth through the modulation of the Akt pathway

Abstract: Abstract. Nitric oxide (NO) is involved in a number of physiological and pathological processes. As an important biological mediator, NO has been the focus of cancer study for its function in tumorigenesis, tumor progression and death. The effects of NO on tumor cells are multifaceted, but many details underlying these effects are not yet well understood. In this study, we demonstrate that NO directly suppresses the growth of BGC-823 cells by inducing G0/G1 phase arrest in a dose-and time-dependent manner. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
3
22
0
Order By: Relevance
“…1B, the proliferation of HepG2 cells was significantly inhibited by NO, with a greater degree of suppression when increasing concentrations of SNP were used. This observation is consistent with a previous study, which demonstrated that NO generated by treatment with SNP inhibited the cell proliferation of gastric cancer cells in a concentration-dependent manner (16).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…1B, the proliferation of HepG2 cells was significantly inhibited by NO, with a greater degree of suppression when increasing concentrations of SNP were used. This observation is consistent with a previous study, which demonstrated that NO generated by treatment with SNP inhibited the cell proliferation of gastric cancer cells in a concentration-dependent manner (16).…”
Section: Discussionsupporting
confidence: 82%
“…NO is known to be involved in diverse processes in numerous physiological and pathophysiological conditions; previous studies have suggested that NO can exert a negative effect on the (10,(12)(13)(14)(15)(16)(17)(18). However, studies concerning the effects of NO on HCC cells are rare.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This was also observed by Sang et al (29). However, when combined with Ad-PKG II infection, SNP and L-arginine treatment markedly inhibited the EGF-induced activation of p-ERK1/2, suggesting that SNP and L-arginine-induced NO/cGMP production exerts an effect on the activation of ERK, but not EGFR.…”
Section: Discussionsupporting
confidence: 62%
“…The degree of inhibition of proliferation and migration capacity was directly proportional to the concentration of the NO donor (Zhou et al, 2016). Similar dose dependent inhibitory results on cellular proliferation have been observed in gastric cancer cells that were treated with an NO donor (Sang et al, 2011). Expression of NO was also observed to block cellular migration of HeLa cells and endothelial cells by blunting the phosphorylation of Akt/PKB (Bulotta et al, 2009).…”
Section: Introductionsupporting
confidence: 75%